Waqf in the 21st Century: The Implementation of Blockchain and Smart Contract Technology - Muhammad Dandy Alif Wildana; Tsumma Lazuardini Imamia (AIBPM Publisher, 2022)
Waqf in its role as Islamic charitable institution has considerable role to sustainable economy, since the initiation of waqf itself started from Muslim for the benefit for all people. Despite its important roles and promising potential, the waqf institution is facing problems which will potentially deprive itself of its full potential. One of the main problems faced by waqf and other charitable institutions is the problem of proper administration of its assets, especially when the contribution to the charitable institution came from various sources. Considering the importance of technology to the life of the 21st century, the same technology may be applied to the enhancement of Islamic charitable institutions such as waqf, in the area of supervise and utilization of waqf assets. This paper employs qualitative methods through literature review to identify the possibility and suitability of technology implementation into waqf institutions. This approach is necessary to explore the potential suitability and the extent of Blockchain and Smart Contracts technology are capable of in improving and enhancing waqf institutions. The possibility of these technologies to be applied to become panacea to the problems that are commonly faced by waqf institutions such as asset administration, transparency, accountability, and governance. The implementation of such technology that offers complete transparency is considered effective against transaction costs and to create efficiency in charitable work of waqf institutions. It is expected that the technology implementation may provide ample room for waqf institutions to evolve into modern Islamic charitable institutions which can answer and adapt to the challenge of the 21st century.Â Keywords: Waqf, Blockchain, Smart Contracts, Waqf Institution, Governance